FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN - Heidy Nivanna; Kartina Natalylova (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain the empirical evidence about factors which influence firm value. The independent variables in this research are profitability, capital structure, ownership structure, firm size, dividend policy, board size, productivity, and liquidity to firm value. This research used multiple regression analysis. The research used SPSS 25. There are 42 non-financial companies listed on Indonesia Stock Exchange that were selected based on certain criteria with the research period from 2016 to 2020.The result of this research shows that independent profitability, capital structure, and productivity has a significant on firm value. Independent ownership structure, firm size, dividend policy, board size, and liquidity has not a significant on firm value